Effect of nanoclay on physical, mechanical, and microbial degradation of jute‐reinforced, soy milk‐based nano‐biocomposites. Issue 2 (30th March 2013) - Behera, Ajaya Kumar; Avancha, Sridevi; Manna, Suvendu; Sen, Ramkrishna; Adhikari, Basudam
<x xml:space="preserve">Abstract</x> Jute‐reinforced, soy milk‐based nano‐biocomposites were fabricated using both natural and organically modified nanoclay to study their effect on physical, mechanical, and degradation properties. Different weight percentages of nanoclays were used to modify soy milk by solution casting process. The jute fibers were then impregnated in modified soy resin and compressed to fabricate nano‐biocomposites. About 5 wt% of organically modified nanoclay‐loaded jute composite showed maximum tensile and flexural strength. X‐ray diffraction and transmission electron microscopy (TEM) analysis of fabricated composites confirmed about the formation of nanostructure. Impact, microhardness, dynamic mechanical analysis results of nano‐biocomposites revealed that nanoclay has influenced to improve such physical and mechanical properties. Microbial degradation study of nano‐biocomposites was carried out in cultured fungal bed. Weight loss, tensile loss, and field emission scanning electron microscopy photographs of composites revealed that composites are biodegradable in nature. The prime advantages of these composite are their eco‐compatibility as jute and soy resin, the basic constituents of composites are biodegradable in nature. These composites can be utilized in automobile, packaging, furniture sectors by replacing nondegradable plastic‐based composite. POLYM. ENG. SCI., 54:345–354, 2014. © 2013 Society of Plastics Engineers